Models of Criminal Liability of Artificial Intelligence: From Science Fiction to Prospect for Criminal Law and Policy in Vietnam - Viet, Trinh Tien (VNU Journal of Science: Legal Studies; Vol 35 No 4DO - 10.25073/2588-1167/vnuls.4257, 2019)
The Industrial Revolution 4.0 (4IR) reflects combination of technologies in physics, digitalisation and biology, shaping a modern world of information technology where virtual and real systems are integrated through worldwide internet connection networks. Artifical Intelligence (AI) and decision making process have seen profound changes. The relevant question is whether criminal liability is applicable to AI entities in the near future given criminal law in many jurisdictions including Vietnam has provided for criminal liability of legal persons as “ abstract entities ”. On this basis, from the criminal law and science fiction approach, the paper initially assumes AI entities as subjects of crimes to explore possible models of criminal liability applicable to AI entities and prospect for changes of criminal law and policy in Vietnam in the future, making recommendations on improvement of legal framework, contributing to crime prevention and protection of human rights in the industrial revolution 4.0. Keywords: Criminal liability; AI entity; model of criminal liability; Criminal Law. References: [1] Gabriel Hallevy, The Criminal Liability of Artificial Intelligence Entities - from Science Fiction to Legal Social Control, Akron Intellectual Property Journal, Vol.4: Iss.2, Article, 2010, https://ideaexchange.uakron.edu/akronintellectualproperty/vol4/iss2/1. [2] I.N. Mosechkin, Artificial Intelligence and Criminal Responsibility: Problems of the Formation of a New Type of Crime Subject, Vestnik SPbGU. Right. 2019.Vol. 10. Vol. 3 (И. Н. Мосечкин, Искусственный интеллект и уголовная ответственность: проблемы становления нового вида субъекта преступления, Вестник СПбГУ. Право. 2019. Т. 10. Вып. 3). [3] Klaus Schwab, Fourth Industrial Revolution, National Political Publishing House - Truth, Hanoi, 2018 (in Vietnamese). [4] Yueh-Hsuan Weng, Chien-Hsun Chen, Chuen-Tsai Sun, Toward the Human-Robot Co-Existence Society: On Safety Intelligence for Next Generation Robots, INT.J.SOC, ROBOT, 2009. [5] Klaus Schwab, The fourth industrial revolution: What it means, how to respond, World Economic Forum, Geneva, 2016. [6] Kevin Kelly, 12 technology trends in the 4.0 era, National Economics University Press, Hanoi, 2018 (in Vietnamese). [7] Matilda Claussén-Karlsson, Artificial Intelligence and the External Element of the Crime: An Analysis of the Liability Problem, JU101A, Final Thesis for the Law Program, Second Cycle, 30 Credits, Spring 2017. [8] Tien Phuc, Five frightening warnings about future AI disasters, http://kenh14.vn/, accessed May 1, 2019 (in Vietnamese). [9] Amir Husain, Cỗ máy tri giác - Kỷ nguyên của trí thông minh nhân tạo, Hoàng Lan dịch, Nxb. Công thương, Hà Nội, 2019. [10] Trinh Tien Viet, Policy and Criminal Law of Vietnam against the challenge of Industrial Revolution 4.0, Proceedings of the National Scientific Conference: “Fourth Industrial Revolution and legal issues posed for the construction and completion of Vietnam legal system”, Ministry of Justice, Hanoi, June 24, 2019 (in Vietnamese). [11] Trinh Tien Viet, From the Beginning to the End of the Criminal Law, Journal of Law, VNU, Episode 34, No.1/2018 (in Vietnamese). [12] Trinh Tien Viet, Crime and criminal responsibility, National Political Publishing House, Hanoi, 2013 (in Vietnamese). [13] Lisa M Storm, Criminal Law, Chapter 4 - “Elements of a crime”, Lulu Publishing Services, United States, 2015. [14] Hoang Phe (chief editor), Vietnamese dictionary, Institute of Linguistics, Danang Publishing House and Dictionary Center, 2006 (in Vietnamese). [15] Nguyen Thi Que Anh, Ngo Huy Cuong (co-editor), The Fourth Industrial Revolution and issues on Vietnam's legal reform, National Political Publishing House - Truth, Hanoi, 2018 (in Vietnamese). [16] Klaus Schwab, Shaping the Fourth Industrial Revolution, translated by Nguyen Van and Thanh Thep, World Publishing House, Hanoi, 2019 (in Vietnamese). [17] Lawrence B. Solum, Legal Personhood for Artifical Intelligences, 70 N.C.L.REV, 1992. [18] Roger C. Schank, What Is AI Anyway?, Al MAG., Winter 1987. [19] George R. Cross, Cary G. Debessonet, An Artificial Intelligence Application in the Law: CCLIPS, A Computer Program that Processes Legal Information, 1 HIGH TECH. L.J., 1986. [20] Ajay Agrawal, Joshua Gans, Avi Goldfarb, Artificial Intelligence in the 4.0 technology revolution, translated by Dao Loi, Labor Publishing House, Hanoi, 2018 (in Vietnamese). [21] Robert P. Fine, Gary M. Cohen, Is Criminal Negligence a Defensible Basic for Criminal Liability? 16 BUFF. L. REv., 1966. [22] Donald Stuart, Mens Rea, Negligence and Attempts, CRIM. L. REV., 1968. [23] Steven J. Frank, Tort Adjudication and the Emergence of Artificial Intelligence Software, 21 SUFFOLK U. L. REV., 1987. [24] Maruerite E. Gerstner, Liability Issues with Artificial Intelligence Software, 33 SANTA CLARA L. REV, 1993. [25] Margaret A. Boden, Has AI Helped Psychology?, The Foundations of Artifical Intelligence, Derek Partridge & Yorick Wilks eds., 2006. [26] Daniel C. Dennett, Evolution, Error, and Intentionality, The Foundations of Artifical Intelligence Derek Partridge & Yorick Wilks eds., 2006. [27] Robert Batey, Judicial Exploration of Mens Rea Confusion at Common Law and Under the Model Penal Code, 18 GA. ST. U. L. REV. 341, 2001. [28] David Levy, The Ethical Treatment of Artificially Conscious Robots, I INT'L J. SOC. ROBOTICS, 2009. [29] Dylan Evans, Can robots have emotions?, Oxford University Press, 2001, http://www.inf.ed.ac.uk/events/hotseat/dylan_position.pdf, truy cập ngày 19/9/2019. [30] Tang Howe Hing, Musa Mailah, Simulator for Control of Control of Autonomous Nonholomich Wheeled Robot, 8 J. OF APPLIED SCI. 2534, 2536, 2008. [31] Le Van Cam, Postgraduate Monograph: Basic issues in Criminal Law science (General Part), Hanoi National University Press, 2005 (in Vietnamese). [32] Dinh Van Que, Commenting on Criminal Code 2015 - Part 1: General provisions, Information and Communications Publishing House, Hanoi, 2017 (in Vietnamese). [33] AI accompanies the threat, http://www.pcworld.com.vn/, accessed September 15, 2019 (in Vietnamese). [34] Andrew Weissmann, David Newman, Rethinking Criminal Corporate Liability, 82 IND. L.J., 2007. [35] Trinh Quoc Toan, Criminal Responsibility of Legal Entities in Criminal Law, National Political Publishing House, Hanoi, 2011 (in Vietnamese). [36] Nguyen Ngoc Hoa, The concept of crime and the determination of criminal liability of commercial legal entities in Vietnam's Criminal Code 2015, Juricprudence Journal, No.2/2016 (in Vietnamese). [37] Nguyen Ngoc Hoa (chief editor), Scientific commentary Criminal Code 2015, amended and supplemented in 2017 (General Part), Justice Publishing House, Hanoi, 2017 (in Vietnamese). [38] Le Cam (chief editor), Vietnam's criminal law from the tenth century to the present: History and reality, Hanoi National University House, 2018 (in Vietnamese). [39] Toby Walsh, 2062 - The era of artificial intelligence, translated by Do Ton Minh Khoa, Ho Chi Minh City General Publishing House, 2019 (in Vietnamese). [40] Politburo, Resolution No.52-NQ/TW on a number of guidelines and policies to actively participate in the Fourth Industrial Revolution, Hanoi, September 27, 2019 (in Vietnamese). [41] Trinh Tien Viet, Continuing to innovate legal thinking in Vietnamese Criminal Law before the challenge of Industrial Revolution 4.0, Journal of Procuratorate Studies, No.4 (31).2019 (in Vietnamese). [42] Trinh Tien Viet (Editor), Vietnam's criminal law before to non-traditional security challenges, National Politice Publishing House, Hanoi, 2019 (in Vietnamese). [43] Trinh Tien Viet, Vietnam's Criminal Policy in the Context of the Fourth Industrial Revolution, Journal of the People's Court, No.7(4).2019 (in Vietnamese). [44] http://www-formal.stanford.edu/jmc/whatisai/node1.html, truy cập ngày 10/10/2019. [45] Houbing Song, Ravi Srinivasan, Tamim Sookor, Sabina Jeschke (ed.), Smart Cities: Foundations, principles and applications, translated by Ngo Thanh Nam, National Political Publishing House - Truth, Hanoi, 2019 (in Vietnamese).